P009 Biologics prescribing trends over 10 years: a retrospective analysis of 799 patients in routine clinical practice. (23rd April 2022) - Zubairi, Rumaisa; Suhaimi, Ak Muhd Adiib Pg; Olsson, Lewis; Smyth, Rachel; Baxter, Derek; Laws, Arrianne; Perry, Martin E
Abstract: Background/Aims: To investigate the biologic prescribing trends for a secondary care patient cohort over a 10-year period for rheumatoid arthritis (RA), psoriatic arthritis (PsA) and spondyloarthropathy (SpA), and compare against current local guidelines. Methods: Departmental database holding patient data was interrogated. Labelled data were consolidated into distinct diagnostic categories of rheumatoid arthritis, psoriatic arthritis and spondyloarthropathy. For ease of analysis, biologic drugs were classified based on their mechanism of action into TNF-alpha blockers (TNFi) and non-TNF-alpha blockers (non-TNFi). Data was collated identifying prescribing trends of first, second and third-line therapies for RA, PsA and SpA. This was compared against local NHS guidelines. Overall cost of biologic prescription for first line therapies was calculated Results: There were 799 patients with a diagnosis of RA, PsA or SpA. Both RA and PsA had the same general prescribing pattern of TNFi as first-line, another TNFi as second-line and non-TNFi as third-line. In SpA, TNFi were mostly used as first, second and third-line. An adalimumab biosimilar was used first-line in 90 (30.6%) RA patients, 42 (35.1%) PsA patients and 32 (32.3%) SpA patients. Methotrexate was co-prescribed with a TNF-alpha blocker in 128 (58.7%) RA patients, 51 (36.4%) PsA patients and 7 (7.7%) SpA patients. TNFi biosimilar drug prescribing has increased from 33% in 2016 to being the most prescribed drug in 2020 (62%). In the entire database cohort of 926 patients, the vast majority are prescribed biosimilars (Table 1 ). The overall cost of biologic prescriptions has reduced by 49% from 2019 to 2020 as the proportion of biosimilars prescribed has almost doubled to 69%. Conclusion: Biologic prescribing patterns are largely in-keeping with current national and local guidelines. The vast majority of patients are on a biosimilar, which has resulted in significant cost-savings for the department. Disclosure: R. Zubairi: None. A. Muhd Adiib Pg Suhaimi: None. L. Olsson: None. R. Smyth: None. D. Baxter: None. A. Laws: None. M.E. Perry: Honoraria; AbbVie, Celltrion Healthcare, Gilead, Lilly, Biogen, Jaansen, Fresenius Kabi.